Development and evaluation of an evidence based smoking cessation app for the Malaysian population: the self-determination theory approach / Budi Aslinie Md. Sabri - Md. Sabri, Budi Aslinie; Berhanuddin, Muhamad Asyraf; Mohamad, Nurul Fasiha; Hassan, Eddy Hasrul (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Tobacco use in Malaysia accounts for 35% of in-hospital deaths, principally from cancer, heart disease and stroke. Thus, effective interventions to support smoking cessation are urgently needed. Smartphones are increasingly receiving attention as a means to assist individuals’ health management through the usage of apps such as smoking cessation apps. However, recent content analysis found that they do not typically adhere to evidence-based principles for smoking cessation and may not sufficiently stimulate autonomous-motivation. This research aims to develop and evaluate a bilingual (Malay/English) evidence-based smoking-cessation app which incorporates self-determination theory features for the Malaysian population. This project was conducted in threephases. Content development phase involved identifying ideal features of an app for behaviour modification in smoking cessation. The technical development phase focused on the technical development of the app which involved creating a programming- language framework. The final phase involved testing and evaluation using the 23-item MARS rating scale which is a validated measure of rating mobile health apps. Preliminary evaluation showed that the MARS total mean score which correspond to a star rating scale was (M=3.35 S.D ±0.50), while the mean score for each domain are as follows; engagement (M=3.30 SD±0.54), functionality (M=3.46 SD±0.64), aesthetics (M=3.46 SD±0.62), information (M=3.39 SD±0.63), subjective quality (M2.91 SD±0.65). More than 90% of the sample felt that this app is likely to increase awareness, knowledge, and motivation, influence change the attitude to smoking cessation in terms of help seeking and behaviour. Thus, the smoking cessation app developed incorporated the three parameters in SDT and fulfils the basic criteria of a health management app as measured by the MARS scale and can potentially aid in smoking cessation activities.